Examining E-Government development effects on corruption in Africa: The mediating effects of ICT development and institutional quality. (May 2020) - Adam, Ibrahim Osman
Abstract: There has been increased development in e-government initiatives in countries across Africa and these initiatives have been linked to reduced corruption levels. Although some studies provide evidence of how e-government development contributes to reduced corruption, few studies have analyzed the mediating effects of ICT development and institutional quality on the e-government development—corruption linkage. Relying on secondary data from multiple sources, we used a hypothesized model and Partial Least Squares Structural Equation Modelling (PLS-SEM) to empirically examine the mediating role of these two factors on e-government development on corruption. Our results show that a significant relationship exists between e-government development and ICT development, e-government development and institutional quality as well as ICT development and corruption. Whilst these were all supported in confirming the effects of ICT development on corruption. The findings demonstrate the significant role ICT development and institutional quality play as mediators of e-government effects on corruption. However, the study's direct effects of e-government on corruption was not significant. The research suggests that the ICT development of countries be strengthened. Furthermore, there is the need for an improved quality of a country's institutions as measures to ensure stronger effects of e-government on corruption. Highlights: This study examines the mediating effects of ICT development and institutional quality on the e-government—corruption linkage. The study developed a conceptual model based on the TOE framework and employed a PLS-SEM approach and data from archival sources. There is a significant relationship between e-government development, ICT development and institutional quality; and not ICT development and corruption. ICT development and institutional quality significantly mediate e-government development effects on corruption. Strengthening of ICT development and improving the quality of public sector institutions will ensure stronger effects of e-government on corruption.